2021
DOI: 10.3389/fpubh.2021.745846
|View full text |Cite
|
Sign up to set email alerts
|

From Cognition to Behavior: Associations of Workplace Health Culture and Workplace Health Promotion Performance With Personal Healthy Lifestyles

Abstract: Introduction: The aim of this study was to explore associations of workplace health culture and workplace health promotion (WHP) performance with employees' healthy lifestyles and health statuses.Methods: In total, 27 enterprises and 1,732 participants were recruited for a cross-sectional designed survey. At the group level, Workplace Health Scorecard was used to measure WHP performance, and it was filled out by the WHP representative at each workplace. At the personal level, a personal questionnaire was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(41 reference statements)
2
7
0
Order By: Relevance
“…Our results showed that perceived engagement of colleagues and management in promoting wellbeing are important determinants for the students’ and workers’ adoption of healthier behaviors, confirming recent results obtained by Chang et al, who found that health promotion activities were positively associated with peers and supervisors’ support in the workplace [ 37 ]. Similarly, for a better promotion of healthy lifestyles among students, it has been shown that the interventions have to be designed taking into account the needs of the recipients.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that perceived engagement of colleagues and management in promoting wellbeing are important determinants for the students’ and workers’ adoption of healthier behaviors, confirming recent results obtained by Chang et al, who found that health promotion activities were positively associated with peers and supervisors’ support in the workplace [ 37 ]. Similarly, for a better promotion of healthy lifestyles among students, it has been shown that the interventions have to be designed taking into account the needs of the recipients.…”
Section: Discussionsupporting
confidence: 90%
“…9,28,48 Peer and coworker support also showed beneficial effects on employee health behavior, such as increased physical activity, healthy eating, and higher employee perceived support. 14,48 Appendix B contains the risk of bias assessment using the JBI Analytical Cross-Sectional Studies.…”
Section: Resultsmentioning
confidence: 99%
“…The Workplace COH scale appeared most frequently as a measure in the observational and intervention studies found in the search conducted for this review (n = 6). 16,26,[35][36][37][38] The WHCS appeared once, 14 COH-INT and COH-EXT appeared two times each. 12,39 Appendix A presents the assessments of risk of bias using the QAVALS for each validity study found in the search.…”
Section: Scale Development and Validity Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, some researchers have tried to develop workplace health culture scales, for example, Chang et al ( 34 , 45 ) developed the workplace health culture scale in Taiwan and has incorporated it into the implementation of workplace health promotion; Jia et al ( 46 , 47 ) has also developed a workplace health culture scale for China, showing application of it. However, little attention has been paid to current workplace health culture research for workers exposed to occupational hazards, such as dust, VOCs, noise.…”
Section: Literature Reviewmentioning
confidence: 99%